A cross sectional study on tobacco and alcohol abuse among medical college students - Singh, Avi; Gupta, Pratibha; Srivastava, Mrinal R.; Zaidi, Zeashan H. (International Journal Of Community Medicine And Public Health, 2017)
Background: Alcohol and tobacco consumption is now considered a serious public health problem. Together, both alcohol and tobacco abuse can cause substantial health related morbidity and mortality. This study was done to assess the patter of tobacco and alcohol abuse among medical college students of Lucknow district, Uttar Pradesh, India. The objective of the study was to assess the pattern of tobacco and alcohol abuse among medical college students of Lucknow district. Methods: A questionnaire based cross sectional study was carried out among 116 first year MBBS students of Era’s Lucknow Medical College, Lucknow. The questionnaire was based on outlines of GATS (Global Adult Tobacco Survey) & Global Information System on Alcohol and Health (GISAH). Results: 61.29% males and 8.24% females abused both tobacco and alcohol. Of all the tobacco users, 70.97% males and 15.29% females consumed cigarettes. In case of alcohol consumption, 80.65% males and 35.29% of females consumed some form of alcohol. Overall 43% of respondents abused alcohol and tobacco to relieve stress. Attempt to quit alcohol and tobacco was at 44.6% overall. Conclusions: This study has shown that alcohol and tobacco are major substances being abused by young medical graduates, in spite of universal knowledge that they are source of major non communicable diseases.